Social Support and Achievement Motivation for College Students during COVID-19 Pandemic - Rizka Fibria Nugrahani; Melly Amalia Vardia; Ria Nur Haliza; Luthfiatus zuhroh (Rifa'Institute, 2022)
The educational field is one of the fields affected by the impact of COVID-19, in which college students include in sub-field that cannot be spared from the effect given by this pandemic. The researchers want to investigate the relationship between social support and achievement motivation on college students during this COVID-19 Pandemic. This research is using correlational quantitative research with a population of 165 college students and the sample research is 65 students in the Study Program of Psychology, Raden Rahmat Islamic University, Malang. A positive relationship between social support and achievement motivation is found in the results of research conducted on the college students of Study Program of Psychology, Raden Rahmat Islamic University, Malang. The higher social support given by the environment shows that the student’s learning motivation is also higher